2009
DOI: 10.1295/polymj.pj2009086
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Photo-Functional Materials Based on Cyclic Oligomers

Abstract: Novel photo-functional materials, such as refractive-index-changing materials, argon fluoride (ArF) resist materials, and electron beam (EB) resist materials, were designed based on the structures of calixarenes, cyclodextrin, and noria. The synthesis and refractive-index properties of calixarene derivatives containing photo-reactive groups, including azobenzene, norbornadiene, anthracene, cinnamate, and chalcone, were examined, and refractive-index changes (Án D 's) of between 0.007 and 0.061 were observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Recently, Kudo and co-workers succeeded in the synthesis of a new ladder cyclic oligomer "noria" (water wheel in Latin) 6 and reported the synthesis and photochemical reactivity of noria derivatives containing t-butoxycarbonyl groups, 7,8 t-butylester groups, 9 acetal groups, 10,11 and adamantyl ester groups. [12][13][14][15] It was found that these noria derivatives had high photo-reactivity and produced clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using EUV exposure tool, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kudo and co-workers succeeded in the synthesis of a new ladder cyclic oligomer "noria" (water wheel in Latin) 6 and reported the synthesis and photochemical reactivity of noria derivatives containing t-butoxycarbonyl groups, 7,8 t-butylester groups, 9 acetal groups, 10,11 and adamantyl ester groups. [12][13][14][15] It was found that these noria derivatives had high photo-reactivity and produced clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using EUV exposure tool, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] It was found that these noria derivatives had high photo-reactivity and produced clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using EUV exposure tool, respectively. [8][9][10][11][12][13][14][15] To enhance the performance of molecular resist materials based on cyclic oligomers, we evaluated their lithographic performances such as sensitivity, resolution and LWR, using EUV and EB exposure systems. Furthermore, we also examined the etching durability of the synthesized molecular resist materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kudo and coworkers have succeeded in the synthesis of a new ladder cyclic oligomer "noria" (water wheel in Latin) [13] and reported the synthesis and photochemical reactivity of noria derivatives containing t-butoxycarbonyl groups [14,15], t-butylester groups [16], acetal groups [17,18], and adamantyl ester groups [19][20][21][22][23]. It was found that these noria derivatives have high photoreactivity and produce clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using an EUV exposure tool [15][16][17][18][19][20][21][22][23]. Moreover, we clarified that the sensitivity of the resist materials was consistent with the structure of the cyclic oligomers such as noria, calixarene dimer, cyclodextrin, and pillar [5]arene [24].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] The use of light as an external stimulus for responsive systems is of particular interest since light is a non-polluting energy sources and can be delivered remotely, precisely in space and time, and even quantitatively. [14] Moreover, the surface wettability, [15] controllable capture and release, [16,17] and refractive index [18] of the hydrogels and the sol-gel transition [19][20][21][22] can be reversibly modulated with light. In recent years, different strategies have been developed to build up photo-responsive hydrogels.…”
Section: Introductionmentioning
confidence: 99%